Author Correction: Distinct effects of social motivation on face evaluations in adolescents with and without autism. Issue 1 (December 2018) - Safra, Lou; Ioannou, Christina; Amsellem, Frédérique; Delorme, Richard; Chevallier, Coralie
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.